Feasibility of offshore wind turbines for linkage with onshore green hydrogen demands: A comparative economic analysis. (1st February 2023) - Kim, Ayeon; Kim, Heehyang; Choe, Changgwon; Lim, Hankwon
Highlights: Offshore wind-based hydrogen production system is investigated. Three options of feasible equipment placement are selected by optimization. Comparative economic analyses are conducted for cases with different conditions. The results indicate the most feasible placement and cost for each case. Optimal cases for two considered regions show possibility of suggested system. Abstract: Imprudent fossil fuel use for getting energy caused serious environmental problems making us necessary to seeking for alternative energy sources which are renewable and sustainable. Using wind energy is currently considered as one of feasible renewable energy sources, however, the problem of noise pollution from the sweep of turbine blades should be solved. As a feasible solution for the noise pollution problem, the construction of wind farms offshore is currently considered. In addition, many factors can change the onshore wind speed, while offshore wind has a higher wind speed and consistency, which leads to higher energy efficiency. However, the remained intermittency of wind energy makes storage media such as H2 necessary, thus, the construction of an offshore wind base H2 production system can be required for protecting the energy security. In this study, a comparative economic analysis is conducted to verify feasible equipment placements of offshore wind-based H2 production systems in various possible cases with different electrolyzer types, wind speeds, and offshore distances. An optimization study for 4 case scenarios with different regions, offshore lengths, and kinds of electrolyzers, was preliminarily conducted to find several placements that are economically optimal in common. For the optimization, a mixed-integer programming tool in Python was used, and as a result, three absolutely economical placements were selected. Then, the comparative economic analysis with considering the selected three cases was conducted indicating the most feasible placement according to the considered offshore length and wind speed, and costs ranged from 1.64 to 4.46 kgH2 −1 . From the optimal cases for considered regions (Ulsan, Magallanes), the system using alkaline electrolyzer can achieve the feasible prices for both regions, while using other types stay in ranges of the current green H2 produced by electrolysis.